Social Obligation of Medical Colleges and Teaching Medical Students Social Responsibility to Health - Piryani, Rano Mal; Piryani, Suneel (Journal of Liaquat University of Medical & Health Sciences, 2023)
World Bioethics Day 2022 was celebrated on 19th October 2022. The theme was 'Social Responsibility and Health'1. This is a reminder for medical schools to emphasize one of the important aspects of Social Responsibility and Health,' i.e. Social obligation of medical colleges and teaching health professions students' social compulsion to health". The medical schools have to develop socially trustworthy and accountable physicians/doctors who volunteer for activities that give contentment to the people and provide socially acceptable healthcare, thereby contributing towards the prosperity of communities2. We may ask two questions to ourselves; 1) Are our medical schools producing socially responsible physicians/doctors who engage themselves in activities contributing towards the bliss, well-being, and fortune of their communities? 2) "Are our medical education programs have state-of-the-art curriculums that produce a positive, constructive effect on the well-being of our communities?